Associations of micronutrients and lipids with prediabetes and glycemic parameters in adolescent girls of the rural DERVAN cohort (DERVAN-9) - Patil, Suvarna; Dervankar, Omkar; Hardikar-Bhat, Pallavi; Joglekar, Charudatta; Bhat, Rohit; Patil, Netaji; Yadav, Arvind (Frontiers in Nutrition, 2024)
Background We investigated the associations of micronutrients and lipids with prediabetes, glycemic parameters and glycemic indices among the adolescent girls of DERVAN cohort study from rural India. Methods: We recruited 1520 adolescent girls aged 16-18y. We measured glycemic parameters (glucose, insulin), lipids (total cholesterol, HDL, LDL and triglycerides) and micronutrients (vitamin B12, folate and vitamin D). Prediabetes was defined using American Diabetes Association criteria (fasting glucose ≥100 mg/dl or HbA1C ≥5.7 %). Glycemic indices (insulin resistance, insulin sensitivity and β cell function) were calculated using homeostasis model. Associations of prediabetes and glycemic indices with micronutrients and lipids were analyzed by multiple logistic regressions. Results: Median age and BMI were16.6 years and 17.6 kg/m2. Overall, 58% had low BMI. Median vitamin B12, folate and vitamin D concentrations were 249.0 pg/mL, 6.1 ng/mL and 14.2 ng/mL respectively. The deficiencies observed were 32.1% for vitamin B12, 11.8% for folate and 33.0% for vitamin D. Median total cholesterol, LDL, HDL and triglycerides concentrations were 148.0 mg/dl, 81.5 mg/dl, 50.8 mg/dl and 61.5 mg/dl respectively. Elevated total cholesterol, LDL, and triglycerides were observed in 4.8%, 4.0%, and 3.8% respectively while low HDL was observed in 12.8%. Prediabetes was observed in 39.7% of the girls. Among lipids, total cholesterol and LDL were higher in girls with prediabetes (p<0.01 for both). In multivariate model containing cholesterol and vitamin B12/folate/vitamin D, prediabetes was associated with high cholesterol. Prediabetes was associated with high LDL independent of folate and vitamin D. Poor insulin secretion was high in those with low vitamin B12. Elevated insulin resistance was associated with low HDL. Likelihood of high insulin sensitivity was reduced in those with high triglycerides. Likelihood of poor β cell function was high in those with high LDL. Statistical interactions between micronutrients and lipids for prediabetes and glycemic outcomes were not significant. Conclusions: There was a substantial deficiency of micronutrients and absence of dyslipidemia. Our results indicate the need of lipid and micronutrient-based interventions in adolescence to improve glycemic outcomes. Maintaining adequate storage of not only micronutrients but also that of lipids in adolescent girls is likely to reduce diabetes risk in adulthood.